PENINGKATAN KEMAMPUAN SISWA MENGUNGKAPKAN GAGASAN MELALUI METODE DISKUSI DALAM PEMBELAJARAN BAHASA INDONESIA KELAS XA SMA NEGERI 1 TOLITOLI UTARA - Samran, Samran (BAHASANTODEA, 2017)
The idea XA grade students of SMA Negeri 1 Tolitoli Utara can be improved. It was revealed from a study of the problem: (1) how the application of the method of discussion to improve the students express ideas in class XA SMA Negeri 1 Tolitoli Utara? And (2) whether the application of the results of the discussion method can improve the students express ideas in class XA SMA Negeri 1 Tolitoli Utara?. This study aims to (1) describe the application of the method of discussion to improve the students express ideas in class XA SMA Negeri 1 Tolitoli Utara and (2) describe the results of applying the method of discussion to improve the students express ideas in class XA SMA Negeri 1 Tolitoli Utara. Methods of data collection using the oral tests, observation and documentation. Qualitative data analysis techniques and quantitative techniques. The results showed that (1) the application of the method of discussion in several stages, The first researcher to prepare articles that will be distributed to students; two researchers set up research pieces express the idea of learning implementation skills; The third researcher prepares a camera to document the activities of teachers and students during the learning process; After that process, the skills students express ideas increased. The percentage of skill express the idea of students has increased at every meeting of the first cycle and the second cycle. Improved skills of students express the idea in the first cycle of 65.75 from 41.33 the initial conditions. In the second cycle increased by 74.67.